Iron in Well Water: Case Study in Dulalowo and Heledulaa Districts - Hendri Iyabu; Anita Muhammad; Jafar La Kilo; Akram La Kilo (Jambura Journal of Chemistry, 2020)
This study aims to determine the iron content of water wells in Dulalowo and Heledulaa, Gorontalo City. Ten well water samples were taken randomly from five different wells in each district. Water samples at each well consist of top, middle, and bottom water. Determination of iron level using Atomic Absorption Spectrophotometer (AAS) at a wavelength of 248.33 nm. The results showed that the iron concentration of well water in Dulalowo was 0.030 (D1), 0.265 (D2), 0.224 (D3), 0.158 (D4), 0.149 ppm (D5). Meanwhile, iron levels in Heledulaa were 0.100 (H1), 0.039 (H2), 0.159 (H3), 0.198 (H4), and 0.235 ppm (H5). These results prove that the Fe content in the well water in the two districts is still fulfil the drinking water standard which is a maximum of 0.3 mg/L iron.